Strength,Weakness,Opportunity and Threat (SWOT) Analysis of Women Entrepreneurship With Reference to Coimbatore, Tamil Nadu - Ramanujam, V. (Prabandhan: Indian Journal of Management, 2010)
Entrepreneurship among women is an important avenue through which women can overcome their subordination within the family and the society as a whole. Therefore, development of entrepreneurship among women has received special attention of the policy makers. In this direction, a special character in the seventh plan has converted the integration of women in economic development. The new industrial policy has stressed the need for conducting special EDPs for women. Besides this, today, a network of institution exists in the country to promote women entrepreneurship. The commercial banks and the financial institutions are an integral part of this network. Many organizations/institutions and associations promote and develop women entrepreneurship by providing financial assistance at concessional rates of interest and also organize industrial fairs and exhibitions. Entrepreneurship Development Programme (EDPs) for women create entrepreneurial awareness among them.